PENGARUH TREATMENT ALKALI TERHADAP KARAKTERISTIK FIBER SABUT KELAPA SAWIT DAN PELEPAH PISANG SEBAGAI BAHAN KOMPOSIT POLIMER - Setiawan, Adhi; Vivin Setiani; Fitri Hardiyanti; Devina Puspitasari (2477 - 6165, 2019)
The use of synthetic fibers in the fabrication of polymer composite materials has a negative impact on the environment. Natural fibers such as palm oil waste and banana pseudostem can be an alternative material for synthetic fibers because they are more economical, high specific strength, and environmentally friendly. The alkali treatment needs to be carried out on fibers for removal of lignin, hemicellulose, and impurity so that they can improve interfacial bonding between the fiber and the polymer matrix. The alkali treatment was carried out through fiber immersion in conditions without NaOH, 5% wt NaOH solution, and 10% wt for 24 hours. Fiber before and after alkalization were analyzed using Scanning Electron Microscope (SEM), X-Ray Difraction (XRD), Fourier Transform Infrared (FTIR), and Thermogravimetric Analysis (TGA) methods. The results showed that alkali treatment was effective in removing the components of lignin, hemicellulose, and impurities in fiber. The result of the SEM showed that the treated fiber surface had a cleaner surface than treatment without fiber. The alkalitreatment process can improve the crystallinity and crystallinity index of the fiber due to amorphous component removal of lignin and hemicellulose. The TGA result of palm oil fiber with alkali treatment and without alkali treatment produced weight loss of 88,2% and 98,4% respectively. This showed that the alkali treatment can increase the thermal resistance of the palm oil fiber.